Oxymorons and Undergraduates’ Repertoire in Literature: Exploring the Nexus - Al-kadi, Abdu; Khalifeh, Areen (Argentinian Journal of Applied Linguistics - ISSN 2314-3576, 2024)
This study probed into figurative speech and its rhetorical effects with a particular focus on oxymorons which have often been conflated with paradoxes. Besides clarifying the difference between the two, an analysis of the academic records of fifty undergraduates and a test of oxymorons were a point of departure to measure their familiarity with such figurative devices. Using the Pearson correlation test, the participants' oxymoron test scores were correlated with their overall scores on the achievement tests of seven literature courses in the academic records. Findings showed a positive correlation coefficient (r=.251), yet it is considerably weak (sig.=079 at α=0.01). Further evidence on the magnitude of the phenomenon was solicited from five faculty members through a focus group discussion. The faculty substantiated the correlational findings, as they hold a view that oxymorons, tied with other linguistic devices, contribute to learners’ repertoire in literature and language in general.